(untitled) (Experimental biology, 2025)
Annotation. In this article the problem of bromine losses during long-term storage of soil samples is studied. For this purpose, soil samples from the Kulunda Plain were studied. The soil cover of this plain is based on chernozems and chestnut soils on watershed areas developing in isolation from groundwater. Semi-hydromorphic and hydromorphic solonts and meadow soils, often saline, are widespread on slopes and in depressions. In soil samples taken according to genetic horizons, humus content, granulometric composition according to Kachinsky method with sample preparation by sodium pyrophosphate, pH - by potentiometric method were determined. The results of the study showed that long-term storage of soil samples leads to very significant losses of gross bromine, the analysis of soil samples for bromine content should be carried out immediately after their drying and rubbing. We have also studied iodine losses. The percentage of iodine losses varies in the range of 2-39.02 %. No strict regularity in the losses was found. Published studies on iodine losses have been carried out quite a long time ago, there are no data on bromine losses at all. Analysis of losses of both halogens for the same soil sample for different storage periods would be very useful for making recommendations on storage periods.